Kinetics of H2O2 Decomposition and Bacteria Inactivation in a Continuous-Flow Reactor with a Fixed Bed of Cobalt Ferrite Catalyst - Nazarii Danyliuk; Viktor Husak; Volodymyra Boichuk; Dorota Ziółkowska; Ivanna Danyliuk; Alexander Shyichuk (Applied Sciences)
As a result of the catalytic decomposition of H2O2, hydroxyl radicals are produced. Hydroxyl radicals are strong oxidants and effectively inactivate bacteria, ensuring water disinfection without toxic chlorinated organic by-products. The kinetics of bacterial inactivation were studied in a laboratory-scale flow catalytic reactor. A granular cobalt ferrite catalyst was thoroughly characterized using XRD and XRF techniques, SEM with EDS, and Raman spectroscopy. At lower H2O2 concentrations, H2O2 decomposition follows first-order reaction kinetics. At higher H2O2 concentrations, the obtained kinetics lines suggest that the reaction order increases. The kinetics of bacterial inactivation in the developed flow reactor depends largely on the initial number of bacteria. The initial bacterial concentrations in laboratory tests were within the range typical of real river water. A regression model was developed that relates the degree of bacterial inactivation to the initial number of bacteria, the initial H2O2 concentration, and the contact time of water with the catalyst.